PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS MODEL 4D DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA KELAS V SEKOLAH DASAR - Idhi Agung Mulyawan; Suriswo Suriswo; Rahmad Agung Nurgraha (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2025)
This study aimed to develop Student Worksheets (LKPD) based on the 4D model (Define, Design, Develop, and Disseminate) in science learning to improve the learning independence of fifth-grade elementary school students. The research employed a Research and Development (R&D) approach using the 4D development model. The study was conducted in elementary schools within the General Sudirman Cluster, Taman District, Pemalang Regency. Data were collected through expert validation, learning independence questionnaires, and pretest–posttest instruments. The feasibility of the developed LKPD was evaluated based on validity, practicality, and effectiveness criteria. The results of expert validation indicated that the LKPD was categorized as valid and suitable for use. Statistical analysis showed an improvement in students’ learning independence after the implementation of the 4D model–based LKPD in the experimental class compared to the control class. These findings indicate that the developed LKPD is feasible, practical, and effective as an alternative instructional material to support student-centered science learning and enhance learning independence among fifth-grade elementary school students.Keywords: Student worksheets, 4D model, learning independence